2020
DOI: 10.1590/1678-7757-2019-0489
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for oropharyngeal dysphagia in cardiovascular diseases

Abstract: Risk factors for oropharyngeal dysphagia in cardiovascular diseases Some conditions consolidated as risk factors for oropharyngeal dysphagia have already been identified in other diseases, such as neurological. Studies on cardiovascular diseases concentrate in individuals in the postoperative period; thus, it is unknown if these same factors occur in individuals hospitalized for clinical or surgical treatment of these diseases. Objective: to correlate predictive risk factors for oropharyngeal dysphagia in indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
3
6
0
2
Order By: Relevance
“…Among clinical predictors, the GCS <13 at admission and in cardiovascular disease were significantly associated with dysphagia in SDH. This is in line with previous studies where cardiovascular disease are identified as predisposing risk factor for dysphagia (15). Furthermore, our data show a significant correlation between dysphagia and the severity of head trauma expressed by GCS.…”
Section: Discussionsupporting
confidence: 93%
“…Among clinical predictors, the GCS <13 at admission and in cardiovascular disease were significantly associated with dysphagia in SDH. This is in line with previous studies where cardiovascular disease are identified as predisposing risk factor for dysphagia (15). Furthermore, our data show a significant correlation between dysphagia and the severity of head trauma expressed by GCS.…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have described the incidence of dysphagia, with the duration of endotracheal intubation after cardiac surgery being a strong predictor of dysphagia [5,7,9,10]. In addition, our study showed that alternative nutrition at the start of rehabilitation was signi cantly associated with MV duration.…”
Section: Discussionsupporting
confidence: 59%
“…A review of the literature on post-extubation dysphagia reveals a variety of causes without consensus [3]. In cardiovascular disease, previous studies have demonstrated that stroke, malnutrition, prolonged orotracheal intubation, and advanced age are predictive risk factors for dysphagia [9][10][11]. However, most studies have reported the incidence of postoperative dysphagia.…”
Section: Introductionmentioning
confidence: 99%
“…Dysphagia and malnutrition are two major issues in the elderly with a negative impact on several pathological conditions, including cardiovascular disorders, cognitive status impairment, immune system downregulation, pressure ulcers, and skeletal muscle system worsening [ 197 , 198 ]. Therefore, effective interventions aimed at improving the nutritional intake and counter malnutrition are mandatory not only to prevent dysphagia-related complications (such as aspiration pneumonia) but also to improve the general health status and the HRQoL of older patients [ 199 ].…”
Section: Oropharyngeal Rehabilitationmentioning
confidence: 99%